THE PSYCHOLOGY OF DECISION-MAKING - Munisa Nazirova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract; The psychology of decision-making is viewed as a cognitive process that results in the choice of an opinion or course of action among several alternative possibilities. A fundamental distinction is made between: quantitative (mathematical) and empirical methods, as well as single-person and multi-person decisions